2006
DOI: 10.1007/s11005-006-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Further Results on the Smoothability of Cauchy Hypersurfaces and Cauchy Time Functions

Abstract: Recently, folk questions on the smoothability of Cauchy hypersurfaces and time functions of a globally hyperbolic spacetime M , have been solved. Here we give further results, applicable to several problems:(1) Any compact spacelike acausal submanifold H with boundary can be extended to a spacelike Cauchy hypersurface S. If H were only achronal, counterexamples to the smooth extension exist, but a continuous extension (in fact, valid for any compact achronal subset K) is still possible.(2) Given any spacelike … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
184
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 17 publications
2
184
0
7
Order By: Relevance
“…The full appreciation of this problem in a background containing a given brane has led to an interesting constraint on the warp factor itself in order to compute the one-loop correction. This criterion is in fully agreement with the more or less recent advances in the characterization of globally hyperbolic spacetimes [13,14]. This paper is organized as follows: in the next section we give an outlook of the basic formalism, indicating the overall procedure to extract the effective lagrangian.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The full appreciation of this problem in a background containing a given brane has led to an interesting constraint on the warp factor itself in order to compute the one-loop correction. This criterion is in fully agreement with the more or less recent advances in the characterization of globally hyperbolic spacetimes [13,14]. This paper is organized as follows: in the next section we give an outlook of the basic formalism, indicating the overall procedure to extract the effective lagrangian.…”
Section: Introductionsupporting
confidence: 76%
“…From a different, but complementary, point of view it was recently shown that a given warped spacetime is hyperbolic (i.e., it is suitable for a well-defined Cauchy problem) if, and only if, the warp factor is of C ∞ class [13,14]. The previous discussion was, then, an illustrative example of the general formalism developed in Refs.…”
Section: Warped Braneworld Peculiaritiesmentioning
confidence: 96%
See 1 more Smart Citation
“…We adopt definitions and results about causal structures as in [44,56], but we take recent results [8,9] into account, too. If (M , g) and (M , g ) are spacetimes and S ⊂ M ∩ M , then J ± (S; M ) (I ± (S; M )) and J ± (S; M ) (I ± (S; M )) indicate the causal (resp.…”
Section: Claudio Dappiaggi Et Almentioning
confidence: 99%
“…Even more, we detail the consequences of these folk questions for the structure of a globally hyperbolic spacetime (Theorem 3.78). Although the description of the smoothing procedure lies out of the scope of the present review (see [44], in addition to the original articles [4,6,7]), the main difficulties are stressed, Remark 3.77.…”
Section: Introductionmentioning
confidence: 99%